Targeting the DNA Damage Response for the Treatment of High Risk Neuroblastoma - Southgate, Harriet E. D.; Chen, Lindi; Curtin, Nicola J.; Tweddle, Deborah A. (Frontiers in Oncology, 2020)
Despite intensive multimodal therapy, the survival rate for high risk neuroblastoma (HR-NB) remains less than 50%. Most cases initially respond to treatment but almost half will subsequently relapse with aggressive treatment resistant disease. Novel treatments exploiting the molecular pathology of NB and/or overcoming resistance to current genotoxic therapies are needed before survival rates can significantly improve. DNA damage response (DDR) defects are frequently observed in HR-NB including allelic deletion and loss of function mutations in key DDR genes, oncogene induced replication stress and cell cycle checkpoint dysfunction. Exploiting defects in the DDR has been a successful treatment strategy in some adult cancers. Here we review the genetic features of HR-NB which lead to DDR defects and the emerging molecular targeting agents to exploit them.